Distribution and Characteristics of Microplastics in Nhue - Day River Basin, Vietnam: 10.32526/ennrj/21/202200244 - Nguyen, Huu Thang; Nguyen, Thi Ha; Hien, To Thi; Hoang, Minh Trang (Environment and Natural Resources Journal, 2023)
The prevalence of microplastics (MPs) in the environment has had a significant impact on ecosystems and posed a major threat to human health. This study investigated the distribution and characteristics of MPs in the Nhue - Day River basin in Vietnam, which is a critical source of biodiversity and used to support the economic growth of about 12 million people. The effect of seasonal variation and anthropogenic activities on the MP abundance was assessed. The findings revealed that the MPs abundance was significant in this study area. The average abundance of MPs in the dry season (754 items/m3) was insignificantly higher than that in the rainy season (706 items/m3) with n=9. The range in the abundance of MPs in the dry and rainy seasons was 49-2,827 and 400-1,133 items/m3, respectively. Microplastics in fiber forms were dominant in both seasons. The majority of the collected MPs were in the 0.5-2.0 mm size range, varying from 71% to 100% of the total MPs depend on sampling point. The total percentage of MPs size 0.3-0.5 mm in the dry season was 56.97% compared to 119.85% in the rainy season, indicating that the MPs were broken into smaller pieces due to UV exposure and weather conditions. Colored items occupied the majority of the MPs. This study can be used to gain a better knowledge of MP pollution in Vietnam’s river water.